2016
DOI: 10.1016/j.juro.2016.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Urodynamic Effects of Autologous Stromal Vascular Fraction Extracted from Fat Tissue with Minimal Ex Vivo Manipulation in a Porcine Model of Intrinsic Sphincter Deficiency

Abstract: These data demonstrate the ability of an autologous stromal vascular fraction to improve the urethral healing process in a large animal model of intrinsic sphincteric deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A recent large animal study confirmed that the SVF is a safe and effective treatment for SUI [20] . SVF contains substantial number of adipose derived stromal/stem cells (ADSCs) as well as leukocytes and endothelial cells [2] .…”
Section: Discussionmentioning
confidence: 90%
“…A recent large animal study confirmed that the SVF is a safe and effective treatment for SUI [20] . SVF contains substantial number of adipose derived stromal/stem cells (ADSCs) as well as leukocytes and endothelial cells [2] .…”
Section: Discussionmentioning
confidence: 90%
“…Adipose‐derived stromal vascular fraction (SVF) is a rich source of AdMSCs . Studies have reported that administration of uncultured SVF could attenuate injury and improve the function of various tissues and organs, such as the heart , kidney , urethral sphincter , etc. Recently, both our team and other groups have demonstrated that, compared with AdMSCs, uncultured SVF exhibited equal effect on attenuating acute renal I/R injury and recovering penile erection .…”
Section: Introductionmentioning
confidence: 99%
“…Boissier et al evaluated the healing abilities of autologous stromal vascular fraction prepared from adipose tissue in a porcine model of intrinsic sphincter deficiency. In this study, stromal vascular fraction injection was associated with a reduction of the urethral injury surface and increased maximum urethral pressure when compared to the respective controls …”
Section: Methodsmentioning
confidence: 62%
“…ADSCs have been tested in preclinical studies in murine, rabbits, and porcine SUI models. Silwal Gautam et al demonstrated that the implantation of ADSCs into cryoinjured female rabbit urethras promoted the recovery of urethral function by myogenic differentiation as well as neuroregeneration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation